New Fungal Records on Psidium guajava from Pakistan: New Fungal Records on Psidium guajava from Pakistan - Abbas, Syed Qaiser; Perveen, Abida; Riaz, Sana; Iftakhar, Thereema; Abbas, Alia (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Aspergillus niger Van Tiegh, Chalara state of Ceratocystis fimbriata Ellis & Halst., Alternaria dianthicola Neergaard and Lasiodiplodia ricini Sacc. are reported for the first time on Psidium guajava from Faisalabad, Pakistan.